Total synthesis of naturally occurring cephalosporolides E/F - Kona, Chandrababu Naidu; Ramana, C. V. (Tetrahedron, 2014)
A modular total synthesis of cephalosporolides E/F featuring sequential epoxide-alkyne coupling and subsequent highly regioselective gold catalyzed alkynolcycloisomerizatio of the resulting alkynetetrol to construct the central spiroketal core has been documented. (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: Alkynetetrol; Cephalosporolide; Epoxide-alkyne coupling; Gold catalysis; Spiroketalization